FRIPRO (FRIHUMSAM) grant awarded by the Research Council of Norway (Principal Investigator / Project Manager) - Fyndanis, Valantis (My University, 2026)
This is a very prestigious and competitive grant awarded by the Research Council of Norway. The success rate that year was 5.7%. The project title is "Morphosyntactic Production in Stroke-induced Agrammatic Aphasia: A Cross-linguistic Machine Learning Approach" (Machine Learning Aphasia). The total budget for this 4-year grant was 9,993,000 Norwegian krones, which corresponds to nearly 1,000,000 euros. I am the PI on this grant.
Keywords: Humanities